AUTOMATED INFORMATION SYSTEMS IN HOTEL BUSINESS AND TOURISM IN UKRAINE - Заміховська, Олена Леонідівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The tourism and hotel business industry informational technologies and systems current state analysis has been presented in article by the example of «Micros-Fidelio» Company Fidelio Front Office system, the global reservation systems Amadeus, Galileo, Sabre і Worldspan and others both with the armoring and hotel service different duties management programs to define the perspective directions of their application in Ukraine and tourism management recommendations design based on the informational technologies and systems using.